Packet-Loss Modeling for Perceptually Optimized 3D Transmission. (25th February 2007) - Cheng, Irene; Ying, Lihang; Basu, Anup
Abstract : Transmissions over unreliable networks, for example, wireless, can lead to packet loss. An area that has received limited research attention is how to tailor multimedia information taking into account the way packets are lost. We provide a brief overview of our research on designing a 3D perceptual quality metric integrating two important factors, resolution of texture and resolution of mesh, which control transmission bandwidth, followed by a suggestion on alternative strategies for packet 3D transmission of both texture and mesh. These strategies are then compared with respect to preserving 3D perceptual quality under packet loss in ad hoc wireless networks. Experiments are conducted to study how buffer size, sending rate, sending intervals, and packet size can affect loss in unreliable channels. A model for estimating the optimal packet size is then proposed. We derive the optimal number of packets based on this model, and relate the theoretical derivations to actual network data.